Republic of San Marino : 2013 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This Article IV Consultation focuses on San Marino's prolonged recession. The global crisis has led to a significant decline in budget revenues. However, San Marino's sizable pre-2008 budget surplus, combined with recent tax measures and efforts to restrain expenditures, have helped contain the deficit at about 3 percent of GDP. Executive Directors noted that San Marino's economy will face financial and fiscal challenges in the near term, as well as uncertain medium-term prospects. Directors considered that, notwithstanding the recent recapitalization, the largest bank will need more capital to meet prudential requirements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: San Marino, Republic of